2019
DOI: 10.31857/s0205-96142019136-51
|View full text |Cite
|
Sign up to set email alerts
|

The present-day seismicity of the White Sea region

Abstract: A revised earthquake catalog has been compiled for the White Sea region for the period between 2005 and 2016. The earthquake parameters were revised using a single velocity model (BARENTS), a single methodological approach (Generalized Beamforming), and all available raw data and bulletins of Russian and foreign seismic stations. The location of two nuclear explosions detonated on July 18, 1985 and September 6, 1988 in northern European Russia for civilian purposes showed that the algorithm for calculating hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The redefinition of hypocenter parameters based on summary bulletin was carried out by using the Generalized beamforming method (Ringdal and Kvaerna 1989) in an improved form implemented in the NAS program (Asming et al 2017;. The algorithm for calculating hypocenters is described in details according to (Morozov et al 2019).…”
Section: Phasementioning
confidence: 99%
See 2 more Smart Citations
“…The redefinition of hypocenter parameters based on summary bulletin was carried out by using the Generalized beamforming method (Ringdal and Kvaerna 1989) in an improved form implemented in the NAS program (Asming et al 2017;. The algorithm for calculating hypocenters is described in details according to (Morozov et al 2019).…”
Section: Phasementioning
confidence: 99%
“…Previous studies have shown (Morozov et al 2019) that using the advanced algorithm implemented in the NAS program in conjunction with the rapid BAR-ENTS model provides relatively accurate hypocenter parameters and allows the use of this technique to recalculate all subsequent earthquakes in the White Sea region. The resulting redefinition of hypocentres does not differ fundamentally from the catalog of the Institute of Seismology in Helsinki, despite the extensive use of other additional data.…”
Section: Phasementioning
confidence: 99%
See 1 more Smart Citation